SiO2 Fibers of Two Lengths and Their Effect on Cellular Responses of Macrophage-like Cells - Smela, Denisa; Chang, Chia-Jung; Hromadko, Ludek; Macak, Jan; Bilkova, Zuzana; Taniguchi, Akiyoshi (Molecules (Basel, Switzerland), 2022)
The immunoreactivity or/and stress response can be induced by nanomaterials' different properties, such as size, shape, etc. These effects are, however, not yet fully understood. This study aimed to clarify the effects of SiO2 nanofibers (SiO2NFs) on the cellular responses of THP-1-derived macrophage-like cells. The effects of SiO2NFs with different lengths on reactive oxygen species (ROS) and pro-inflammatory cytokines TNF-α and IL-1β in THP-1 cells were evaluated. From the two tested lengths, it was only the L-SiO2NFs with a length ≈ 44 ± 22 µm that could induce ROS. Compared to this, only S-SiO2NFs with a length ≈ 14 ± 17 µm could enhance TNF-α and IL-1β expression. Our results suggested that L-SiO2NFs disassembled by THP-1 cells produced ROS and that the inflammatory reaction was induced by the uptake of S-SiO2NFs by THP-1 cells. The F-actin staining results indicated that SiO2NFs induced cell motility and phagocytosis. There was no difference in cytotoxicity between L- and S-SiO2NFs. However, our results suggested that the lengths of SiO2NFs induced different cellular responses.
Keywords: cytokiny; Tumor Necrosis Factor-alpha; THP-1-derived macrophage-like cells; makrofágy; Macrophages; Reactive Oxygen Species; cytotoxicity; oxid křemičitý; THP-1 buňky; SiO2 nanofibers; Humans; Silicon Dioxide; Cytokines; lidé; THP-1 Cells; reaktivní formy kyslíku; immunoreactivity; TNF-alfa